AN ANALYSIS OF ILLOCUTIONARY ACTS UTILIZED BY LECTURERS IN LISTENING CLASSES - Indira Karin Putri Rudy; Sri Wulandari; Entusiastik (Esteem Journal of English Education Study Programme, 2025)
This study examines how lecturers use illocutionary acts in listening classes at the Islamic University of Kadiri, analyzing them through Searle’s framework. A qualitative approach was used to identify the most frequent illocutionary acts, their roles in classroom interactions, and the impact of cultural and institutional contexts. Data were collected via classroom observations, audio-video recordings, and semi-structured interviews with lecturers from two classes (Class A and Class B). The findings indicate that directives were the most common illocutionary acts, accounting for 69.45% of utterances in Class A and 53.57% in Class B, followed by assertives (15.85% in Class A and 30.56% in Class B) and expressives (13.25% in Class A and 15.08% in Class B), which fostered a positive learning atmosphere. Commissives were rare, appearing only in Class A (1.44%), while declaratives were minimal, present only in Class B (0.79%). This research highlights the lecturers' strategies in guiding students and creating a supportive learning environment. It emphasizes the need for tailored communication strategies to improve student engagement and comprehension in listening classes. Future research could explore similar analyses in diverse educational settings to broaden these insights, especially in the context of Islamic universities in Indonesia.